Knowledge, attitudes, and practices of healthcare workers on antimicrobial resistance and antibiotic use in Erbil city, Iraq: a cross-sectional study - Mohammed Saleh Abdelkarim , Mahdi; Issa Al-Bana, Haitham (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Antimicrobial resistance (AMR) is a growing global health threat, with predictions of a substantial rise in AMR-related deaths over the coming decades. Healthcare workers (HCWs) are central to the fight against AMR through their prescribing and counselling practices. This study assessed the knowledge, attitudes, and practices (KAP) regarding antibiotic use and AMR among HCWs in Erbil City, Iraq, and examined how these vary across professions. Methods: A cross-sectional study was conducted in five government hospitals in Erbil City, Iraq: Erbil Teaching Hospital, West Emergency Hospital, Rizgary Teaching Hospital, Raparin Hospital, and Gynecology and Maternity Hospital. Physicians, pharmacists, dentists, and nurses were recruited using a convenience sampling approach. A total of 408 healthcare workers were interviewed face-to-face using a standardized questionnaire between September 2024 and March 2025. Data were analyzed using SPSS version 27. Results: Participants' ages ranged from 19 to 99 years (mean 34.0 ± 8.6 years), and years of professional experience averaged 10.3 ± 8.1 (range 1–35). Males comprised 46.3% of the sample and females 53.7%. Physicians (38.5%) and nurses (30.1%) were the most represented professions, and most participants (83.8%) held permanent positions. Knowledge of AMR was inconsistent: although 82.4% correctly identified prevention of post-operative infection as an appropriate use of antibiotics, misconceptions about antibiotic use remained common. Adherence to prescribing guidelines, discussion of antibiotic use with patients, and knowledge scores all differed significantly across professions (P <0.001), with physicians scoring highest and nurses lowest. Conclusion: There are substantial gaps in the knowledge, attitudes, and practices of healthcare workers in Erbil City regarding antibiotic prescribing. Targeted interventions, particularly among nurses, are needed to strengthen antimicrobial stewardship and curb the emergence and spread of AMR.